A new species of tereancistrum (Monogenea: Dactylogyridae), parasite of prochilodus lineatus (characiformes: Prochilodontidae) from southeast brazil - Leite, Lucas Aparecido Rosa [UNESP]; Pelegrini, Larissa Sbeghen [UNESP]; de Azevedo, Rodney Kozlowiski; Abdallah, Vanessa Doro (FapUNIFESP (SciELO), 2020)
A new species of Tereancistrum Kritsky, Thatcher & Kayton, 1980 collected of Prochilodus lineatus gills from the Batalha River, Tietê-Batalha basin, São Paulo State, Brazil is described. The new species can be distinguished from its congeners mainly by the configuration of the ventral bar, which has an anvil-shaped characteristic with corrugated anterior projection. Tereancistrum takemotoi n. sp. is morphologically similar to T. toksonum Lizama, Takemoto & Pavanelli, 2004 in terms of their dorsal bars (Y-shaped), their dorsal anchors with divergent roots (superficial and deep) wherein their deep root rather elongated, and by the fact that they both have the male copulatory organ counterclockwise. However, only T. takemotoi n. sp. presents the male copulatory organ with 2¼ rings and shows undulations in the anterior margin of the dorsal bar. These undulations are absent in T. toksonum (which only has 1¼ rings). This is the fourth Tereancistrum species described for P. lineatus and the first described for the region from the Tietê-Batalha basin.
Uma nova espécie de tereancistrum (Monogenea: dactylogyridae), parasito de prochilodus lineatus (characiformes: prochilodontidae) do sudeste do brasil
Keywords: Batalha river; Dactylogyridea; Freshwater fish; Gills parasite; Platyhelminthes; Taxonomy